DETERMINANTS OF PATIENTS’ SATISFACTION LEVEL REPORTING CHRONIC KIDNEY DISEASE CLINICS ESTABLISHED IN THAILAND - Taptagaporn, Sasitorn; Mongkolsomlit, Sirima; Rakkapao, Nitchamon; Kaewdok, Teeraphun; Wattanasoei, Supang (Journal of Ayub Medical College Abbottabad, 2021)
Background: Patients’ satisfaction is considered to be major predictor used for the assessment of the overall quality of the healthcare services. The current study aims to evaluate the patient’s level of satisfaction reporting Chronic Kidney Disease clinics (CKDC) under the Policy of the Ministry of Public Health, Thailand providing the care for Chronic Kidney Disease (CKD) patients in the public hospitals by a multidisciplinary health professional team. Methods: A cross sectional study was conducted from January-December 2017. A two-stage sampling technique was adopted. A validated and reliable questionnaire was administered to 258 CKD patients during their visit to the CKD clinic from 134 public hospitals in 12 regional service providers in Thailand to elicit their satisfaction level. The satisfaction was scored and described into four aspects: services, place and facilities, health professional staff, and medical equipment and supplies. Data was analysed using frequency, mean, standard deviation, and Mann-Whitney U test and Kruskal-Wallis test were used to determine whether there was a significant difference among the variables in terms of patients’ satisfaction. This study was ethically approved from the Ethics Review Committee of Thammasat University, Thailand (COA. No. 254/2560). Results: Most of the respondents 53.9% were female ranging from 21-88 years with a mean age of 64.69 years SD 13.14. The mean score of satisfaction for all CKD patients was 3.11±0.44 (out of 4) categorized in a good satisfaction level. The satisfaction level of the service aspect was least in comparison to others. Among all the variables a significant difference in satisfaction level was found in terms of duration of the disease (Ï‡2 =10.52, p=0.03*). Conclusion: This study has demonstrated levels of satisfaction with the CKD clinic that could tailor for the significant implications and challenges in improving healthcare service policy further.